Branded women in U.S. television : when people become corporations - Bjelskou, Peter (Critical studies in television., 2015)
This book examines product placement and brand integration in U.S. television. Using examples from 1950s television sponsorship to The Real Housewives, Bjelskou illustrates how the commercialization of TV programing affects both formats and narratives and how these genres are in conversation with contemporary political and social environments